Exploring the Impact of Islamic Education Philosophy on Emotional Intelligence Development in Muslim Students - Ali, Muhammad Usman; Wathoni, Hamzani; Muslim, Mohd (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2023)
This library study aims to examine the effect of Islamic education philosophy on the emotional intelligence development of Muslim students. This study highlights the potential synergy between Islamic education philosophy and the components of emotional intelligence through a systematic review of relevant literature. Existing literature suggests that the Islamic education philosophy, with its emphasis on moral values, character development, self-awareness, and interpersonal skills, can foster emotional intelligence in Muslim students, although few empirical studies investigate this relationship specifically. The findings highlight the need for additional empirical research to establish causal relationships and identify effective strategies for integrating Islamic education principles into educational practices to improve emotional intelligence. Future studies can contribute to evidence-based practices that promote emotional intelligence within Islamic educational contexts by incorporating cultural and contextual factors and fostering interdisciplinary collaboration, thereby enhancing the overall well-being and success of Muslim students.